Effect of Sweet Potato Leaves Extract on the Survival of Tilapia in the Transportation Process - Ellys Triyani; Andri Iskandar; Annisa Apriliani Wahyudi; Wiyoto Wiyoto (Universitas Islam Lamongan, 2025)
Transportation is a follow-up activity in cultivation that is useful for moving fish to new habitats. The transportation system used is a closed system that relies on oxygen in it. This system has disadvantages, such as fish being easily exposed to stress due to decreased water quality in the media and disruption of fish metabolism. Therefore, an alternative strategy is needed by anesthetizing the fish to reduce movement and metabolism during transportation. The anesthetic used is sweet potato leaves which contain saponins (21,50%), flavonoids (1,30%), and polyphenols (4,0947 mg/g). This research aims to apply the use of Ipomoea batatas sweet potato leaf extract mixed into water media in the transportation process of prospective black tilapia broodstock Oreochromis niloticus. The research used a completely randomized design (CRD) method consisting of three replications and four treatments, namely treatment K (control), P2 (2 mg/L), P4 (4 mg/L), and P6 (6 mg/L). The results of the research can be concluded that the best treatment in this study was P6 which showed higher survival rates and lower blood glucose levels compared to other treatments (P<0.05), while the water quality parameters between treatments did not significant different.